Emergence of competitive dominant ammonia-oxidizing bacterial populations in a full-scale industrial wastewater treatment plant - Layton, Alice C. (2005)
Ammonia-oxidizing bacterial populations in an industrial wastewater treatment plant were investigated with amoA and 16S rRNA gene real-time PCR assays. Nitrosomonas nitrosa initially dominated, but over time RI-27-type ammonia oxidizers, also within the Nitrosomonas communis lineage, increased from below detection to codominance. This shift occurred even though nitrification remained constant.